The Effect of Swedish Abdominal Massage on Constipation Scale in Stroke Patients - Dewi Suryandari; Dian Nur Wulanningrum; Diyanah Syolihan Rinjani Putri (Indonesian Journal of Global Health Research, 2025)
In stroke, sudden neurological and functional damage occurs due to reduced or interrupted blood flow to the brain caused by clots or plaque in the blood vessels. Stroke clients experience neuromotor deficits, causing symptoms of paralysis on one side of the body with a level of weakness, so they are at risk of constipation. Constipation is a common problem in patients. Nurses have an important role in overcoming constipation in patients who are on mechanical ventilation during treatment, one of the non-pharmacological therapies that can be done by nurses to overcome constipation is abdominal massage. Objective: Knowing the effect of swedish massage on the constipation scale in stroke Patients at Dr. Moewardi Hospital. Method: This research uses the quasy experiment method with a pretest and posttest approach without control. The population in this study were stroke patients at Dr. Moewardi Hospital. The sampling technique in this study was the Non-Probability Sampling technique with the total sampling technique, namely taking samples equal to the number of populations that have met the inclusion and exclusion criteria made by the researcher. The sample in this study was 20 respondents. Univariate analysis in this study consisted of respondent characteristics, constipation scale before massage and constipation scale after massage. Bivariate analysis in this study was to determine the effect of Swedish massage on constipation scale in stroke patients at Dr. Moewardi Hospital. Data normality test showed pre-normal constipation (p value> 0.05), post-abnormal constipation (p value <0.00) so the data was not normal, so the bivariate test used the Wilcoxon test. Pre and post intestinal peristaltic data were normal, so the bivariate test used the Paired Sample T Test. Results: The analysis results show a p-value of 0.009. Conclusions: There is an effect of Swedish massage on the constipation scale of stroke patients.